1,3,5,7-Tetra(Bpin)azulene by Exhaustive Direct Borylation of Azulene and 5,7-Di(Bpin)azulene by Selective Subsequent Deborylation - Nishimura, Hidetaka; Eliseeva, Maria N.; Wakamiya, Atsushi; Scott, Lawrence T. (Synlett, 2015)
Exhaustive borylation of azulene with excess bis(pinacolato)-diboron (B2pin2) under conditions that promote equilibration of the borylated azulenes provides a convenient one-step synthesis of 1,3,5,7-tetra(Bpin)azulene as the major product. The Bpin substituents at positions 1 and 3 can be conveniently removed from 1,3,5,7-tetra-(Bpin)azulene by treatment with trifluoroacetic acid at room temperature to give 5,7-di(Bpin)azulene. The utility of 5,7-di(Bpin)azulene as a synthetic precursor to 5,7-disubstituted azulenes that are otherwise difficult to access is demonstrated by Suzuki coupling to give the previously unknown 5,7-diphenylazulene.
Keywords: iridium; palladium; catalysis; C–H activation; Suzuki coupling; synthesis; methodology; functionalization